(untitled) (Annals of Medical Research, 2021)
Aim: This study aims to investigate the changes in the post-op NRT thresholds of two different implant electrodes of the same brand positioned laterally within the scala tympani, and the pre-modiolar locations, using the same round window approach.Material and Methods: After CI operation NRT measurements conducted at different times on the Nucleus® CI422 nucleus slim straight and Nucleus® CI24RE electrode types of two different electrode models.Results: The number of patients who received the Nucleus® CI24RE (ST) electrode and the Nucleus® CI422 nucleus slim straight were 26 (33.3%) and 56 (66.7%), respectively. NRT values tended to decrease from the basal part of cochlea towards an apex at any time of evaluation in both types of cochlear implants. Conclusion: There was a difference between Nucleus® CI24RE and Nucleus® CI422 nucleus slim straight groups in terms of NRT thresholds. Nucleus® CI422 nucleus slim straight electrode yielded lower NRT threshold levels.